2018
DOI: 10.1002/pbc.27245
|View full text |Cite
|
Sign up to set email alerts
|

Dose–volume metrics and their relation to memory performance in pediatric brain tumor patients: A preliminary study

Abstract: These preliminary findings call into question the value of prescribed dose for characterizing treatment intensity; they also suggest that biophysical dose has only a limited advantage compared to physical dose when calculated for specific regions of the brain. We discuss the implications of the findings for evaluating and understanding the relation between RT and neurocognitive functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In particular, processing speed showed the greatest vulnerability post-PRT CSI, consistent with XRT outcomes research associating higher RT doses to larger volumes of brain with less favorable neurocognitive outcomes. 6,[28][29][30][31] Working memory vulnerability was also identified. The solidly stable performance in verbal and perceptual reasoning domains in this group suggests that the decline observed in FSIQ is likely driven by declines in processing speed and working memory.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, processing speed showed the greatest vulnerability post-PRT CSI, consistent with XRT outcomes research associating higher RT doses to larger volumes of brain with less favorable neurocognitive outcomes. 6,[28][29][30][31] Working memory vulnerability was also identified. The solidly stable performance in verbal and perceptual reasoning domains in this group suggests that the decline observed in FSIQ is likely driven by declines in processing speed and working memory.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Findings from a cohort of 14 pediatric patients with brain tumors treated with proton therapy with 2 years of follow-up suggested that word-pair delayed recall was associated with both left and right hippocampal doses. 27 There are also data suggesting that the hippocampal volume is reduced in survivors of pediatric brain tumors and that this volume reduction is associated with a decline in memory. 28 …”
Section: Discussionmentioning
confidence: 99%
“…53 Additionally, CRT overlap with the hippocampus further portends a poorer neurocognitive prognosis in survivors, similar to anticipated toxic effects of chemotherapy on the hippocampus. 46,54,55 Proton-based CRT is one modifying factor that continues to undergo investigation as a means to decrease CRT-related neurocognitive injury. Proton CRT has less radiation scatter and ideally treats a more targeted volume with decreased radiation exposure to surrounding healthy tissue.…”
Section: Neurocognitive Injury In Relationship With Radiationmentioning
confidence: 99%